1950
DOI: 10.1017/s0022029900005835
|View full text |Cite
|
Sign up to set email alerts
|

426. Some bacteriological aspects of the deterioration of pasteurized milk

Abstract: 1. Examinations have been made of milk pasteurized by the L.T. ‘Holder’ and H.T.S.T. processes using the same original bulk raw milk. In the preparation of samples care was taken to eliminate the possibility of post-pasteurization contamination. It was hoped that any differences found would be due solely to the effects of the pasteurizing processes above.2. Samples were examined by (a) colony counts and coliform tests when fresh and after ageing at 18°C. for 24 and 48 hr., (b) methylene-blue and resazurin redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

1951
1951
1986
1986

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…Also, the relatively higher resistance of certain groups of excretal streptococci towards pasteurisation (63 C for 30 min) than most of the coliform bacteria would seem to explain in a great part the results obtained with pasteurised milk and ice cream. Although heat-resistant coliforms are Correlation between coliformii results and excretal streptococci index in raw and pasteurized milk knoown to exist, their incidence in efficiently pasteurised milk was found to be low (Crossley, 1946;Ashton, 1950). Not all of the milk or ice cream samples which produced acid and gas in MacConkey's broth showed the presence of fecal streptococci.…”
Section: Resijlts and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the relatively higher resistance of certain groups of excretal streptococci towards pasteurisation (63 C for 30 min) than most of the coliform bacteria would seem to explain in a great part the results obtained with pasteurised milk and ice cream. Although heat-resistant coliforms are Correlation between coliformii results and excretal streptococci index in raw and pasteurized milk knoown to exist, their incidence in efficiently pasteurised milk was found to be low (Crossley, 1946;Ashton, 1950). Not all of the milk or ice cream samples which produced acid and gas in MacConkey's broth showed the presence of fecal streptococci.…”
Section: Resijlts and Discussionmentioning
confidence: 99%
“…This may be explained oni the basis of various possibilities which are known to play a part in coliform results. It is possible that such samples contained coliforms of nonfecal origin (Wilson et al, 1935) or that false positive acid and gas results were produced by organisms other than coliforms (Ashton, 1950). Recently, Williams (1956) showed that a combination of S. faecalis and aerobic sporeformers, for example, Bacillus subtilis, can produce acid and gas in milk cultures.…”
Section: Resijlts and Discussionmentioning
confidence: 99%
“…Much of this has recently been summarized in some published work carried out at Shinfield by Franklin (1965), but nevertheless, I must-even if briefly-refer to this earlier work. Ashton (1950) showed that dye reduction tests on raw milk were of little value in predicting the keeping quality of pasteurized milk. Many years before this we had found little relationship between plate counts and reduction time when examining raw milk.…”
Section: Pasteurized Milkmentioning
confidence: 99%
“…Possibly, if the refrigeration resources of the dairy are not adequate, an infection with sweet curdling organisms may also occur. Ageing of raw milk a t 4-10" before pasteurization has been shown to lead to increases in the thermoduric peptonizing flora and to reduce the keeping quality of the pasteurized milk (Ashton, 1950).…”
Section: (D) the After-effects Of Refrigerationmentioning
confidence: 99%